2014
DOI: 10.1093/aje/kwu326
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Secondary Data Sources to Identify Parkinson Disease Against Clinical Diagnostic Criteria

Abstract: Parkinson disease (PD) is the second most common neurodegenerative disorder. Its diagnosis relies solely on a clinical examination and is not straightforward because no diagnostic test exists. Large, population-based, prospective cohort studies designed to examine other outcomes that are more common than PD might provide cost-efficient alternatives for studying the disease. However, most cohort studies have not implemented rigorous systematic screening for PD. A majority of epidemiologic studies that utilize p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
(36 reference statements)
2
17
0
Order By: Relevance
“…Because our goal was to describe prescription drug utilization and patterns, we chose a PD case definition that optimized sensitivity first and then specificity. Prior studies have compared the accuracy of Medicare claims in the identification of PD; however, they employed slightly different methodologies . Noyes and colleagues compared PD diagnosis by selfā€report (ā€œHave you ever been told you have Parkinson's disease?ā€) against physicianā€only claims for ICD code 332.0 and found that the highest positive predictive value was 74%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because our goal was to describe prescription drug utilization and patterns, we chose a PD case definition that optimized sensitivity first and then specificity. Prior studies have compared the accuracy of Medicare claims in the identification of PD; however, they employed slightly different methodologies . Noyes and colleagues compared PD diagnosis by selfā€report (ā€œHave you ever been told you have Parkinson's disease?ā€) against physicianā€only claims for ICD code 332.0 and found that the highest positive predictive value was 74%.…”
Section: Discussionmentioning
confidence: 99%
“…This method optimizes sensitivity (range, 64-89%) over specificity (range, 28-99%) based on prior studies that have evaluated the diagnostic accuracy of administrative claims compared with the gold standard of either self-reported diagnoses or review of clinical information. [13][14][15][16] However, to further improve the specificity of our case definition, and to decrease the risk of misclassification of secondary parkinsonian syndromes in our cohort, we also excluded individuals with a history of schizophrenia (ICD 295) or secondary/atypical parkinsonism (ICD codes 332.1 and 333.X). Similar case ascertainment methods have been used in previous health care utilization studies of Medicare populations.…”
Section: Study Design Data Source and Samplementioning
confidence: 99%
“…Algorithms validated in adults have been demonstrated to be inaccurate for the identification of children with the same disease [31,32], and some algorithms are more sensitive for older adults compared with younger adults [33]. A recent study by Jain et al [34] highlighted the limitations of using Medicare claims data as the main secondary source of identifying Parkinson's disease (PD) compared to PD identified via self-report or use of anti-parkinsonian medications. In a systematic review, St. Germaine-Smith et al [35] concluded that in order to ensure that population-based studies of neurological conditions that used administrative datasets were interpreted correctly, the accuracy of the case-definition should be carefully scrutinised.…”
Section: The Methods Section Of the Reportmentioning
confidence: 99%
“…Safarpour et al 2 used routinely collected administrative data provided by Medicaid in their analysis. 9 Safarpour et al 2 identified their PD cases using the ICD-9 332 diagnostic code from physician/ carrier claims, excluding beneficiaries with a concomitant diagnosis of Parkinson-plus syndrome. A number of validated methods for accurately identifying PD in Medicaid and related databases exist, 8-10 as contrasted with selfreport (e.g., "Have you ever been told you had Parkinson disease?").…”
mentioning
confidence: 99%
“…A number of validated methods for accurately identifying PD in Medicaid and related databases exist, 8-10 as contrasted with selfreport (e.g., "Have you ever been told you had Parkinson disease?"). 8,9 Whether or not missed cases of PD were systematically different in their demographic characteristics or outcomes is unknown, and we do not know how relevant the reported 2002-2005 data are to practice in 2015. One longitudinal populationbased study reported that only 40% of self-reported PD cases had typical neuropathology findings in a small postmortem sample, 10 although another study suggested greater specificity of self-report in a relatively young PD cohort when compared against clinical assessment.…”
mentioning
confidence: 99%